Evaluation of Erosion Wear of Ash Handling Pipes - Khan, Abrar Ali (My University, 2012)
Erosion wear is a very common problem in the ash handling pipelines of the coal fired thermal power plants. Mild steel is most commonly used as the piping material in thermal power plants because of its low price and good mechanical properties. Therefore, mild steel was chosen as one of the testing material. Steel 202 was chosen as the second testing material. Steel 202 is cheap and has better properties than mild steel. Erosion wear plays an important role in design and operation of slurry transport system. The present work reports experimental investigation on slurry erosion of mild steel and steel 202 with and without tungsten carbide coating in a slurry pot tester with fly ash and bottom ash slurry mixed in water as erodent. The coating was done with high velocity oxy-fuel (HVOF) thermal coating of thickness of 250μ-300μ. Effect of parameters such as speed at 700, 1000 and 1400rpm with concentration of fly ash at 20%, 40% and 60% by weight in water and for time duration of 60, 90, 120,150 and 180 minutes was calculated. Analysis of weight-loss data and examination of eroded surfaces by scanning electron microscopy was done for coated and uncoated material. Steel 202 reported less erosion wear than mild steel .WC coated mild steel and steel 202 reported less erosion wear than uncoated mild steel and steel 202. The analysis of eroded samples was done using SEM. Signatures of microcutting, fracture of well-bonded WC grains, and fragmentations were observed on the eroded surface of WC-12Co coating, while signatures of formation of ploughing, lips, shearing of platelet, formation of crater, and micro-cutting were observed on the eroded surface of bare mild steel and steel 202.
M.E. (Production and Industrial Engineering)
Keywords: Erosion Wear; Ash Handling Pipes